Microsphere Overview - Sah, Shiv Kumar; Vasia, Mrs.; Yadav, Rajkumar Prasad; Patel, Sunny; Sharma, Mukesh (Asian Journal of Pharmaceutical Research and Development, 2021)
The aim of developing continuous or managed delivery mechanisms has always been to minimise dosage duration, resulting in improved patient compliance and less side effects. Microspheres have been shown to minimise dosage, side effects, administration frequency, and the risk of dose dumping. As a result, patient compliance has improved.Targeted drug delivery mechanisms aim for a specific location in the body to maximise drug concentration in a specific tissue or organ, thus improving the drug's therapeutic effectiveness. Microspheres have promised targeted or managed drug distribution in the body for decades, and have shown to be superior to traditional drug delivery. The goal of this review different aspects of the microparticulate drug delivery system along with types of microspheres and methods of preparation and different applications as targeted or controlled drug delivery system.